2018
DOI: 10.1038/s41419-018-1077-9
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor β upregulated by lncRNA-H19 to promote cancer stem-like properties in papillary thyroid carcinoma

Abstract: Estrogen receptor β (ERβ) plays critical roles in thyroid cancer progression. However, its role in thyroid cancer stem cell maintenance remains elusive. Here, we report that ERβ is overexpressed in papillary thyroid cancer stem cells (PTCSCs), whereas ablation of ERβ decreases stemness-related factors expression, diminishes ALDH+ cell populations, and suppresses sphere formation ability and tumor growth. Screening estrogen-responsive lncRNAs in PTC spheroid cells, we find that lncRNA-H19 is highly expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 46 publications
2
59
0
Order By: Relevance
“…The mean H19 was increased in 19 frozen ATC tissues compared to the 19 patients with benign thyroid nodes who underwent thyroidectomy and/or or FNA tissues. Our study was agreed to Li's and Wächter's [24,25] but contrary to the Lan's [20]. The expression level and role of H19 in different tissues are different.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The mean H19 was increased in 19 frozen ATC tissues compared to the 19 patients with benign thyroid nodes who underwent thyroidectomy and/or or FNA tissues. Our study was agreed to Li's and Wächter's [24,25] but contrary to the Lan's [20]. The expression level and role of H19 in different tissues are different.…”
Section: Discussionsupporting
confidence: 73%
“…In PTC tissues, H19 was significantly higher than paired paracancerous tissue or normal tissues, and overexpression of H19 was correlated with higher tumor burden of PTCs [18]. Li et al also found that H19 is highly expressed in papillary thyroid cancer stem cells (PTCSCs) and PTC tissue specimens, which is correlated with poor overall survival [24]. However, Lan et al have reported that H19 is downregulated in PTC tissues and in PTC cell lines compared to controls, and decreased H19 expression was correlated with lymph node metastasis [20].…”
Section: Discussionmentioning
confidence: 98%
“…Estrogen receptor overexpression, however, has not only been found in the well-known estrogen dependent tumour types, such as breast, endometrial and ovarian cancer. Altered estrogen and / or progesterone receptor expression has been documented for example in thyroid cancer [12][13][14][15], Hodgkin's lymphoma [16][17][18], B-cell malignancies [19,20], brain tumours [21][22][23][24][25], prolactinoma [26,27], melanoma [28][29][30][31], lung cancer [32,33], colorectal cancer [34][35][36], gastric cancer [37] and liver cancer [38,39].…”
Section: Determinants Of Estrogen Effect On Tissuesmentioning
confidence: 99%
“…Former studies have illustrated that lncRNAs promoted PTC development and by regulating stemness 37 39 . CSCs are identified as crucial participants in tumor progression 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%